Das war die DDR, Teil 1: Ich war Bürger der DDR . That Was GDR, part 1: I Was a Citizen of the GDR - Nickel, Gitta; Schwarze, Wolfgang (Germany, 1993)
This television documentary series offers the most comprehensive visual account of the 40-year history of a separate East Germany. The series covers all the important cultural, economic and political developments, from the founding of the GDR to the popular upheavals that finally brought the Berlin Wall down. Part 1: In this simple phrase, "I was a citizen of the GDR," lie countless individual life stories. Former citizens of the German Democratic Republic tell of their personal feelings, experiences and attitudes toward the GDR as well as both material difficulties and the dominance of the State. They reflect on important, painful and contradictory historical events such as the uprising on the 17th of June 1953, the rise and fall of the Berlin Wall and the suppression of the Prague Spring in 1968. They also convey the sense of the hopes pinned on Mikhail Gorbachev's Perestroika. A historical collage in the form of stories told by East Germans both prominent and unknown.